Tea: aspects related to the quality and prospects - Lima, Juliana Domingues [UNESP]; Mazzafera, Paulo; Moraes, Wilson da Silva; da Silva, Reginaldo Barboza [UNESP] (My University, 2009)
Camellia sinensis, which is cultivated in more than 30 countries, assuming a great socioeconomic importance. Several studies suggest that tea has protective effects against cancer and cardiovascular disease, due to the presence of polyphenols called catechins, which are oxidized enzymatically during the processing of the black tea, generating a mixture consisting mainly of theaflavins, theasinensins and thearubigins. The world production of tea has increased more than the demand, causing a drop of the price which, together with the increase in cultivation costs has shown a need for high productivity and quality. Nevertheless, there is not yet an efficient and accurate criteria to predict the quality of tea and agronomic practices which contribute to the increase in quality. In Brazil, the culture of tea is concentrated in the Ribeira Valley - SP, and almost all the production is exported. Despite the Brazilian product is not of high quality, it has achieved good prices in the international market. The Brazilian production, the production area and the number of tea industries are decreasing in recent years, clearly indicating the need for investments.
Chá: Aspectos relacionados à qualidade e perspectivas
Keywords: Agronomic practices; Black tea; Camellia sinensins; Catechins; Green tea